2015
DOI: 10.1016/j.abb.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Excited state conformational dynamics in carotenoids: Dark intermediates and excitation energy transfer

Abstract: A consideration of the excited state potential energy surfaces of carotenoids develops a new hypothesis for the nature of the conformational motions that follow optical preparation of the S2 (1(1)Bu(+)) state. After an initial displacement from the Franck-Condon geometry along bond length alternation coordinates, it is suggested that carotenoids pass over a transition-state barrier leading to twisted conformations. This hypothesis leads to assignments for several dark intermediate states encountered in femtose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(90 citation statements)
references
References 87 publications
(149 reference statements)
5
80
0
Order By: Relevance
“…However, the debate on the characterization of the S* state is still ongoing. Beck et al [102] reinterpreted the radiationless decay of carotenoids after photoexcitation up to the S 2 state by referring to a model derived from studies of polymethine cyanines [103]. They suggested that the S* state can be assigned to a low-lying S 1 state structure with intramolecular charge transfer character and a pyramidal conformation (figure 5).…”
Section: The Other Forbidden Singlet Excited States (S* S X and X)mentioning
confidence: 99%
“…However, the debate on the characterization of the S* state is still ongoing. Beck et al [102] reinterpreted the radiationless decay of carotenoids after photoexcitation up to the S 2 state by referring to a model derived from studies of polymethine cyanines [103]. They suggested that the S* state can be assigned to a low-lying S 1 state structure with intramolecular charge transfer character and a pyramidal conformation (figure 5).…”
Section: The Other Forbidden Singlet Excited States (S* S X and X)mentioning
confidence: 99%
“…This point strongly suggests that the chromophore-binding site in a protein host can play a dominant role in controlling the quantum yield for photochemistry by selecting the ground-state conformation. 56 A similar suggestion, that the protein raises the quantum yield for photochemistry by "pretwisting" the chromophore in the ground state, was made by Kukura et al 32 on the basis of femtosecond stimulated Raman studies of the photochemistry of retinal PSB in rhodopsin. Additionally, the electrostatic environment of the binding site can control the minimum-energy path on the excited-state potential energy surface, the adiabaticity of the barrier crossing event, and the solvent friction that retards torsional motion.…”
Section: ■ Discussionmentioning
confidence: 90%
“…An alternative quenching sensitisation process has then to be sought. A possible explanation relies on the relatively high yield of trans‐cis isomerisation observed in model polyenes molecules upon population of carotenoids S 1 state , which would positively correlate with the higher quenching sensitisation yield detected when these states are excited directly. We stress that, in any case, these species are not the actual quenching sites.…”
Section: Discussionmentioning
confidence: 99%